2016
DOI: 10.1103/physrevb.93.054515
|View full text |Cite
|
Sign up to set email alerts
|

Critical quadrupole fluctuations and collective modes in iron pnictide superconductors

Abstract: The multiband nature of iron pnictides gives rise to a rich temperature-doping phase diagram of competing orders and a plethora of collective phenomena. At low dopings, the tetragonal-to-orthorhombic structural transition is closely followed by a spin density wave transition both being in close proximity to the superconducting phase. A key question is the nature of high-Tc superconductivity and its relation to orbital ordering and magnetism. Here we study the NaFe1−xCoxAs superconductor using polarization-reso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
154
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(173 citation statements)
references
References 138 publications
18
154
0
1
Order By: Relevance
“…Recent Monte Carlo studies have examined the scaling structure of nematic and related QCPs (31,32) as well as the role of fluctuations in promoting superconductivity (33,34). Moreover, the model is particularly topical, as there is good evidence that a nematic QCP underlies the superconducting dome in many (possibly all) of the Fe-based superconductors (35)(36)(37)(38)(39)(40)(41) and possibly even the cuprate high-temperature superconductors (42)(43)(44).…”
mentioning
confidence: 99%
“…Recent Monte Carlo studies have examined the scaling structure of nematic and related QCPs (31,32) as well as the role of fluctuations in promoting superconductivity (33,34). Moreover, the model is particularly topical, as there is good evidence that a nematic QCP underlies the superconducting dome in many (possibly all) of the Fe-based superconductors (35)(36)(37)(38)(39)(40)(41) and possibly even the cuprate high-temperature superconductors (42)(43)(44).…”
mentioning
confidence: 99%
“…First, the buildup of the lowenergy B 2g Raman intensity upon cooling is the dominant feature observed experimentally above T s . [31][32][33] Second, both orbital and the nematic fluctuations have B 2g symmetry. Indeed, Eq.…”
Section: B Raman Couplingmentioning
confidence: 99%
“…30 In this paper we do not attempt to resolve the above controversy, but rather explore the consequences of the nematic fluctuations as observed in recent Raman experiments. [31][32][33] Even though the region of the phase diagram contained between T s and T SDW is either absent or quite tiny, the dynamical nematic fluctuations revealed by Raman spectroscopy kick in far into the paramagnetic phase up to room temperatures. The Raman spectroscopy is essentially a dynamic probe of electronic correlations of prescribed symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Xa, The normal-state electronic states in many iron-based superconductors show strong in-plane anisotropic properties that break the fourfold rotational symmetry of the lattice due to the presence of nematic order [1][2][3][4][5][6][7][8][9]. The nematic order is typically accompanied by a structural transition at T s following an antiferromagnetic (AF) transition at T N ≤ T s , except for FeSe where no AF order is found [10,11].…”
mentioning
confidence: 99%
“…It is shown that the nematic order may go through a zero-temperature order-to-disorder quantum phase transition as shown by elastoresistance [3,9], elastic constants [4,5], and Raman scattering [7,8]. The nematic susceptibility shows divergent behavior with the form of (1/T ) γ around optimal doping [3,5,[7][8][9]20]. However, the value of γ is found to be 1, which suggests that the nematic QCP may result in a mean-field scaling.…”
mentioning
confidence: 99%